Sex Differences in the Immune System Become Evident in the Perinatal Period in the Four Core Genotypes Mouse - Ghosh, Mrinal K.; Chen, Kuan-hui E.; Dill-Garlow, Riva; Ma, Lisa J.; Yonezawa, Tomohiro; Itoh, Yuichiro; Rivera, Lorena; Radecki, Kelly C.; Wu, Quiming P.; Arnold, Arthur P.; Muller, H. Konrad; Walker, Ameae M. (Frontiers in Endocrinology, 2021)
We have used the four core genotypes (FCG) mouse model, which allows a distinction between effects of gonadal secretions and chromosomal complement, to determine when sex differences in the immune system first appear and what influences their development. Using splenic T cell number as a measure that could be applied to neonates with as yet immature immune responses, we found no differences among the four genotypes at postnatal day 1, but by day 7, clear sex differences were observed. These sex differences were unexpectedly independent of chromosomal complement and similar in degree to gonadectomized FCG adults: both neonatal and gonadectomized adult females (XX and XY) showed 2-fold the number of CD4+ and 7-fold the number of CD8+ T cells versus their male (XX and XY) counterparts. Appearance of this long-lived sex difference between days 1 and 7 suggested a role for the male-specific perinatal surge of testicular testosterone. Interference with the testosterone surge significantly de-masculinized the male CD4+, but not CD8+ splenic profile. Treatment of neonates demonstrated elevated testosterone limited mature cell egress from the thymus, whereas estradiol reduced splenic T cell seeding in females. Neonatal male splenic epithelium/stroma expressed aromatase mRNA, suggesting capacity for splenic conversion of perinatal testosterone into estradiol in males, which, similar to administration of estradiol in females, would result in reduced splenic T cell seeding. These sex steroid effects affected both CD4+ and CD8+ cells and yet interference with the testosterone surge only significantly de-masculinized the splenic content of CD4+ cells. For CD8+ cells, male cells in the thymus were also found to express one third the density of sphingosine-1-phosphate thymic egress receptors per cell compared to female, a male characteristic most likely an indirect result of Sry expression. Interestingly, the data also support a previously unrecognized role for non-gonadal estradiol in the promotion of intra-thymic cell proliferation in neonates of both sexes. Microarray analysis suggested the thymic epithelium/stroma as the source of this hormone. We conclude that some immune sex differences appear long before puberty and more than one mechanism contributes to differential numbers and distribution of T cells.